Combination therapy of TKIs and ICIs for the treatment of anaplastic thyroid carcinoma - Zhang, Xi; Lu, Hongzhi; Lv, Yuanshi; Gao, Hong; Jin, Hui (Frontiers in Oncology, 2025)
ObjectiveTo explore the efficacy of combination therapy of tyrosine kinase inhibitor (TKIs) and immune checkpoint inhibitor (ICIs) in patients with anaplastic thyroid carcinoma (ATC).MethodThis study enrolled 7 patients with ATC between June 2020 and June 2024, and conducted follow-up for a minimum of 6 months post-treatment, with the longest follow-up duration reaching 4 years. Patients received treatment with the TKI-Anlotinib and the ICI-Sintilimab, administered every 3 weeks in a treatment cycle.ResultFollowing treatment, among the 7 patients, the primary lesion in 3 patients who had not undergone thyroidectomy exhibited significant shrinkage, the lung metastases in 5 patients with pulmonary involvement significantly regressed, and the lateral cervical lymph node metastases in all patients demonstrated notable reduction.ConclusionCombination therapy of TKIs and ICIs for the treatment of ATC patients can be highly effective and bringing better therapeutic outcomes and quality of life for patients.